Pervasive information gathering and data mining for efficient business administration. (October 2016) - Garrigos-Simon, Fernando J; Llorente, Roberto; Morant, Maria; Narangajavana, Yeamduan
Following a multidisciplinary perspective (that combines the literature from management, information systems, marketing and engineering telecommunications perspectives), the purpose of this article is to create and analyze a conceptual framework and to propose a new methodology that encompasses different techniques for pervasive information gathering in hotels and for identifying clients' habits. Focusing on the future of hotels, this work presents new technologies for hotels suitable for correlating the customers' on-site activities with online activities including passive location tracking using Wi-Fi devices' connectivity, customer satisfaction evaluated via facial or voice recognition using inbuilt cameras/microphones altogether with data mining analysis. Moreover, this article explains how multidisciplinary consumer behavior can be analyzed by data mining to include this information in the vacation marketing approach for efficient business administration.